(3GdcGed aj eYQaI GdVYaGA GdeMOKjf Ch GdcGed aj GdLQM hGdJYOjds - (3GHf YOj , YHO Gddg Hf YOj Hf YHO Gddg Hf eMeO Hf GdeHGQc GdLQLGfj, CHh CMeO,J (B365 (3g` s
(3ChdgG (B:s
(3jHJOF HbGSe Hf YHOGddg GdYeQGfi s
(3Vef eLehY , JQJjHgG (B: (3GdeLdO GdKGfi hGdCNjQs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B82s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B280 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B207 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1382s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs